CHEMICAL CHARACTERIZATION OF DENTAL PASTES CONTAINING LATEX FROM MACLURA TINCTORIA (L). GAUD. (MORACEAE) (CIPEEX, 2025)
Maclura tinctoria (L.) Gaud. (Moraceae) is a medicinal plant popularly known as "moreira", used in folk medicine for its astringent, anti-inflammatory, and analgesic effects. Thus, this research aims to chemically characterize and compare the elements present in different paste formulations, using the combination of calcium hydroxide with Maclura tinctoria latex at different time periods (24 h to 6 months), as well as calcium hydroxide combined with saline solution, through laboratory analysis of scanning electron microscopy (SEM) and EDX microanalysis. The results showed that in the pastes of latex with calcium hydroxide, the Ca element remained with high peaks, not being present in the pastes of latex in its isolated form. It is concluded that M. tinctoria latex did not demonstrate interference in the dissociation of calcium hydroxide and in the concentration of the Ca element when compared to the calcium hydroxide paste with saline solution.
Keywords: Maclura tinctoria; traditional folk medicine; Scanning Electron Microscopy